Antibacterial properties of a novel nano-silver loaded poly(styrene-co-acrylic) composites. Issue 9 (November 2021) - Cao, Ruge; Zhai, Xuqing; Li, Xueyang; Zhao, Xiaoyu
To prevent microbial contamination in foods and medical tools, we prepared a novel antibacterial material nano-silver loaded poly(styrene-co-acrylic) (nAg-PSA) composites by in situ reductions. The nAg-PSA was characterized by scanning electron microscope, transmission electron microscopy, energy dispersive X-ray spectroscopy and thermogravimetric analysis. The antibacterial properties of nAg-PSA against Escherichia coli and Staphylococcus aureus were systematically evaluated, and the underlying mechanism was investigated. Results showed that the silver nanoparticles were successfully loaded onto PSA microspheres, highly dispersed on the surface of nAg-PSA nanoparticles. The nAg-PSA nanoparticles all showed significant antibacterial effects, among which nAg-PSA4 had maximum diameters of inhibition zones against the Gram-negative E. coli (1.18 mm) and the Gram-positive S. aureus (1.29 mm), respectively, which closely related to the size and density of silver nanoparticles covered on the surface.